Analysis of Indonesian Employment Conditions 2020–2025: Challenges, Digital Transformation, and Labor Absorption Strategies - Citra Wulandari Manik; Hilkia Natasya Br Ginting; Mahlina Putri Manurung; Nadya Nafisha; Putri Andini Nasution; Salsabila; Dwi Nabila Putri; Aulia Putri Ramadhani; Noni Rozaini (Perpustakaan dan Penerbitan Unismuh Makassar, 2026)
This study examines the dynamics of Indonesia’s employment conditions during the 2020–2025 period by analyzing post-pandemic labor market recovery, the impact of digital transformation, and strategies for improving labor absorption. A qualitative approach employing a Systematic Literature Review (SLR) and descriptive analysis of secondary data was adopted. Data were collected from Statistics Indonesia (BPS), the International Labour Organization (ILO), the World Bank, OECD reports, and recent peer-reviewed publications related to employment and digital transformation. The findings indicate that Indonesia experienced a substantial labor market recovery, as reflected by the decline in the Open Unemployment Rate from 7.07% in 2020 to 4.76% in early 2025, accompanied by an increase in total employment to 145.77 million workers. Nevertheless, structural challenges remain significant, particularly the dominance of informal employment (56.1%), persistent skills mismatches, and widening digital competency gaps. Digital transformation has generated new employment opportunities in technology-based industries, e-commerce, and digital services while simultaneously increasing the risk of job displacement through automation and artificial intelligence. The study identifies three strategic policy priorities for strengthening labor absorption: reforming vocational education and digital skills development, expanding inclusive digital infrastructure to support labor-intensive sectors and MSMEs, and establishing flexible yet protective labor market regulations. The study concludes that maximizing Indonesia’s demographic dividend requires stronger collaboration among government, industry, and educational institutions to enhance workforce adaptability, improve labor productivity, and ensure that digital transformation contributes to inclusive employment and sustainable economic growth rather than widening socioeconomic inequalities.